2019
DOI: 10.3390/ijms20122855
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of lncRNAs and circRNAs Reveals the Metabolic Specialization in Oxidative and Glycolytic Skeletal Muscles

Abstract: The biochemical and functional differences between oxidative and glycolytic muscles could affect human muscle health and animal meat quality. However, present understanding of the epigenetic regulation with respect to lncRNAs and circRNAs is rudimentary. Here, porcine oxidative and glycolytic skeletal muscles, which were at the growth curve inflection point, were sampled to survey variant global expression of lncRNAs and circRNAs using RNA-seq. A total of 4046 lncRNAs were identified, including 911 differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Their study revealed a new post-transcriptional regulatory layer that could promote the understanding of the molecular mechanisms of muscle ber development in different breeds of pigs. Shen studied the circRNA expression pro les of the psoas major muscle and the longissimus dorsi muscle of 178-day-old Qingyu pigs and identi ed 810 circRNAs, of which 137 were differentially expressed [24]. These circRNAs may be involved in the regulatory network of muscle ber type.…”
Section: Discussionmentioning
confidence: 99%
“…Their study revealed a new post-transcriptional regulatory layer that could promote the understanding of the molecular mechanisms of muscle ber development in different breeds of pigs. Shen studied the circRNA expression pro les of the psoas major muscle and the longissimus dorsi muscle of 178-day-old Qingyu pigs and identi ed 810 circRNAs, of which 137 were differentially expressed [24]. These circRNAs may be involved in the regulatory network of muscle ber type.…”
Section: Discussionmentioning
confidence: 99%
“…Kotb et al identified and annotated many circRNAs in the skeletal muscles of Rhesus monkey via RNA-seq and verified the downregulation of mmu_circ_017332, mmu_ circ_014269, mmu_circ_015060, mmu_circ_006895, and mmu_circ_014509 during aging in monkeys [35]. In addition, previous reports have identified circFUT10, circLM07, circSVIL, circRBFOXO2, circFGFR2, circZFP609, circFGFR4 and circSNX29 were involved in myogenesis [36][37][38][39][40][41][42][43]. In our study, we highlighted that circBBS9 was a potential biomarker of aging-associated muscle dysfunction and may potentially mediate the amelioration effects exerted by exercise.…”
Section: Discussionmentioning
confidence: 89%
“…Since longer QTL will introduce more false positive results, we assumed that 1 Mbp on either side of the peak (center of the QTL) would be adequate to encompass the underlying genes or polymorphisms responsible for the QTL (Shen et al 2019) and cut QTL that are longer than 2 Mbp down to 2 Mbp. The adjusted QTL and the QTL less than 2 Mbp were considered as the effective QTL regions and were used for subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%
“…2018; Shen et al . 2019), but no deep integration analysis of QTXs information in pigs has been reported. In this study, we focused on the fat‐related traits in pig, and constructed a unified physical map.…”
Section: Introductionmentioning
confidence: 99%